Production of Lyophilized Preparation of Anti-Rabies Immunoglobulin and Examination of Its Main Properties - E. G. Abramova; N. N. Kochkalova; A. K. Nikiforov; A. Yu. Butyrskii; Yu. V. Ivanov; N. V. Sinitsyna; T. A. Mikheeva; L. N. Minaeva; M. V. Galkina; L. V. Savitskaya; S. V. Generalov; M. N. Kireev; et al. (Проблемы особо опасных инфекций, 2011)
Presented are data on examination of physical, chemical and biological characteristics of lyophilized preparation of geterologous anti-rabies immunoglobulin. Dry and original liquid forms of immunoglobulin were comparatively analyzed. The lyophilized form was shown to preserve main properties during long-term storage.